New proofs of Konig's bipartite graph characterization theorem - Salman Ghazal (Indonesian Journal of Combinatorics, 2017)
We introduce four new elementary short proofs of the famous König's theorem which characterizes bipartite graphs by absence of odd cycles. Our proofs are more elementary than earlier proofs because they use neither distances nor walks nor spanning trees.